2009
DOI: 10.1242/jcs.049148
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of β4-integrin expression by epigenetic modifications in the mammary gland and during the epithelial-to-mesenchymal transition

Abstract: . (1999). p53 inhibits alpha 6 beta 4 integrin survival signaling by promoting the caspase 3-dependent cleavage of AKT/PKB. J. Cell Biol. 147, 1063-1072. Cameron, E. E., Bachman, K. E., Myohanen, S., Herman, J. G. and Baylin, S. B.(1999). Synergy of demethylation and histone deacetylase inhibition in the re-expression of genes silenced in cancer. Nat. Genet. 21, 103-107.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 45 publications
5
71
0
1
Order By: Relevance
“…In contrast, histone deacetylation by HDACs promotes chromatin compaction and gene repression (17,25,27). Evidence shows that TGF-␤1 can regulate epigenetic modifications to regulate target genes in diverse cell types, including vascular smooth muscle cells (42), ovarian (63), and mammary epithelial cells (61), immune cells (66), and fibroblasts (15). Reports show that histone modifications including H3K9Ac and H3K4 methylation (H3K4me) play a role in PMA-induced laminin gene expression in rat mesangial cells (35) and in inflammatory gene expression in tubular cells from acute renal injury models (34,65).…”
Section: F607 Histone Acetylation In Tgf-␤1-mediated Actionsmentioning
confidence: 99%
“…In contrast, histone deacetylation by HDACs promotes chromatin compaction and gene repression (17,25,27). Evidence shows that TGF-␤1 can regulate epigenetic modifications to regulate target genes in diverse cell types, including vascular smooth muscle cells (42), ovarian (63), and mammary epithelial cells (61), immune cells (66), and fibroblasts (15). Reports show that histone modifications including H3K9Ac and H3K4 methylation (H3K4me) play a role in PMA-induced laminin gene expression in rat mesangial cells (35) and in inflammatory gene expression in tubular cells from acute renal injury models (34,65).…”
Section: F607 Histone Acetylation In Tgf-␤1-mediated Actionsmentioning
confidence: 99%
“…Together, the results indicate that NRP2 is required for proper branching morphogenesis of mouse mammary glands and invasion of mammary ducts into fat pads. Branching morphogenesis in 3D culture is mediated by VEGF 165 and requires NRP2 We used NMuMG cells, which are immortalized, normal mouse mammary gland epithelial cells (Yang et al, 2009), to study the potential role of NRP2 in branching morphogenesis and mammary gland development in more detail. Initially, we focused on a possible connection between branching morphogenesis and an EMT based on previous expression analyses of branching morphogenesis in the mouse mammary gland, in which the EMT-inducing transcription factors Snail (Snai1-Mouse Genome Informatics) and Twist were found to be upregulated more in TEBs than in mature ducts (KourosMehr and Werb, 2006).…”
Section: Nrp2 Is Required For Proper Branching Morphogenesis In the Dmentioning
confidence: 99%
“…Whilst there has been significant advances in our knowledge of a range those genes altered by epigenetic changes in prostate cancer, at present studies examining epigenetic alteration of integrin gene expression and its role in prostate cancer are limited (Chen et al, 2009;Park et al, 2004;Uhm et al, 2010;Yang et al, 2009). In experiments utilising bisulphite sequencing of cloned DNA derived from prostate cancer cell lines conducted in our laboratory, we have observed that altered methylation of the ITGA2 promoter is associated with altered gene expression (data not shown).…”
Section: Dna Methylation and Chromatin Remodellingmentioning
confidence: 86%
“…At present, there is no evidence that the α 6 gene promoter is regulated by altered methylation. However, Yang et al (2009) have reported the β 4 integrin is regulated by both methylation changes and histone modifications. Further, the loss of β 4 expression in mammary gland cells is associated with increased methylation of the β 4 promoter and an increase in repressive histone modifications and EMT (Yang et al, 2009).…”
Section: Dna Methylation and Chromatin Remodellingmentioning
confidence: 99%
See 1 more Smart Citation